2015
DOI: 10.1016/j.econmod.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Public policy and growth in Canada: An applied endogenous growth model with human and knowledge capital accumulation

Abstract: a b s t r a c t a r t i c l e i n f oEvidence suggests that the Canadian economy is over-shadowed with lagging productivity growth and that its innovation strategy lacks a market-oriented focus; and is unbalanced and biased. We study this problem with the aid of a dynamic general equilibrium model driven by analytics of endogenous growth and investigate the viable policy options and assess the interactions between knowledge driven growth, acquisition of human capital, and the role of strategic public policy fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
5
0
1
Order By: Relevance
“…Overall, we observe that the growth paths display a fluctuating structure toward equilibrium. Revelation of such fluctuating structures toward equilibrium is recognized also in the comparable literature by Sequeira (2011) and Voyvoda and Yeldan (2011). In general, human capital employed by R&D activities displays a more fluctuated structure than human capital employed by final good production.…”
Section: Analysis Of Alternative Subsidization Programsmentioning
confidence: 76%
See 1 more Smart Citation
“…Overall, we observe that the growth paths display a fluctuating structure toward equilibrium. Revelation of such fluctuating structures toward equilibrium is recognized also in the comparable literature by Sequeira (2011) and Voyvoda and Yeldan (2011). In general, human capital employed by R&D activities displays a more fluctuated structure than human capital employed by final good production.…”
Section: Analysis Of Alternative Subsidization Programsmentioning
confidence: 76%
“…As new research leading to new innovations is conducted, the index set {A} expands. Following the idea in Funke and Strulik (2000) and based on applications of Sequeira (2010Sequeira ( , 2011 and Voyvoda and Yeldan (2011), this is achieved in the R&D sector as follows: New research is generated solely by human capital allocated to the production of new ideas (research personnel), H A and excludes decreasing returns as well as the scale effects of A. 1 The research productivity of each researcher is a factor w .…”
Section: Production Activitiesmentioning
confidence: 99%
“…The abilities, knowledge, experiences, and skills that employees possess, and which are valuable to their employers are collectively referred to as human capital (Knudsen & Lien, 2023). According to Voyvoda & Yeldan (2015), the development of human capital is essential for fostering innovation, productivity, and long-term business growth. Employees must undergo retraining and upskilling in order to be able to use new systems and processes as a result of the shift in skill and knowledge requirements brought about by the introduction of new technologies (David, 2015).…”
Section: Human Resourcesmentioning
confidence: 99%
“…Mohamed (2016) assessed the impact of the KE on long‐term economic growth in the Egyptian economy for the period 1980–2014, using Granger causality to test the four components of the KE (i.e., human capital, innovation, economic growth, and institutional regime); the results indicate a causal relationship between the KE and economic growth. Voyvoda and Yeldan (2015) investigated and assessed the interactions between knowledge‐driven growth, acquisition of human capital, and role of strategy in public policy for Turkey's economy and reported that the government expenditure on education and other capital investments has a direct link with growth in Turkey. Similarly, Edvinsson and Söderberg (2011) investigated the dynamics of the knowledge economy before the industrial revolution in Sweden and Western Europe and reported the price of essential goods as an important driver of the KE.…”
Section: Literature Reviewmentioning
confidence: 99%